Ozone therapy improves the antioxidant status of high-density lipoproteins and reduces lipid peroxidation in coronary artery disease patients. (Ozone Therapy Global Journal, 2013)
Coronary arte ry disease (CAD) is the mo st c om mo n c aus e of death in westernsocietie s. Epid emiological studies have found that p l asma concentration of highdensity lipoproteins (HDL) correlates inversely with the incidence of CAD. The qualityand functionality of HDL, more than quantity, appears to be an important predictor ofantiatherogenic properties of these particles. Epidemiological evidence demonstratesthat low HDL-paraoxonase activity is associated with increased risk of cardiovasculardisease. Evidence that antioxidant enzymes, and other subcellular activities could bemodulated by low doses of ozone is now proven and support itsclinical a pplication.The aim of the prese nt s tudy was to evaluate t he effect of ozone therapy onparaoxonase 1 lactonase activity and lipid damage in CAD patients. We included 52pa tients in the clinical study. The first g roup (n=26) recei ved 20 sessi ons of ozone(40μg/mL; 200 mL) by rectal insufflation, meanwhile the second one was treated withoxygen only (n=2 6, co ntro l group). A t the end of the study we determ i nedspectrophotometri cally the paraoxonase-lactonase activity, and the LDL and serumsusceptibility to lipid peroxidation. The results showed that ozone therapy was able tored uce the malondialdehyde levels in trea ted p atie nts at the same tim e tha tparaoxonase 1 lactonase a ctivity w as sign i ficantly (p